Davutoğlu Doctrine and Turkish Foreign Policy in the Middle East: A Critical Constructivist Analysis - Miranto, Edi (Jurnal Politik Profetik, 2017)
Referring to the argument that a state’s historic background and geographic location in the world are inherent elements of its foreign policy narrative which constitutes its identity, this article examined and brought narratives on the reconstruction of Turkish foreign policy towards the Middle East which was directed by a foreign policy doctrine of Davutoğlu as defined Davutoğlu Doctrine. Using a critical constructivist perspective, it contends that Davutoğlu’s foreign policy vision for Turkey is an attempt to reconstruct the international role and responsibilities of Turkey through a transformed identity based on a reinterpretation of its historical heritage and geographic location. This article concluded that the Davutoğlu Doctrine’s vision was not only an endeavor to overturn the traditional tendencies in Turkish foreign policy, but also in any ways, is a task of identity transformation. Further, this new activism has led to a shift in the axis of its foreign policy from the Western orientation to a more assertive, strict independent foreign policy that is central to the Davutoğlu Doctrine. Finally, Davutoglu Doctrine can be recognized that it has reconstructed Turkey’s state identity to reshape Turkish foreign policy onwards to the Middle East aiming to reposition Turkey as the global representative and a key player in the region.